Cardiovascular Reactivity to Acute Mental Stress in Post Ovulatory Females - Rajbhandari Pandey, Karishma; Khadka, Rita; Agrawal, Kopila; Paudel, Bishnu Hari; Panday, Dipesh Raj (Journal of Nepal Health Research Council, 2021)
Background: Female hormones fluctuate with the phases of menstrual cycle. Estrogen, which has attributes in cardio-protection, is secreted less during luteal phase. In post-ovulatory phase, days 1-2 before menstruation has minimal female hormone influence due to less secretion. Mental stress subjected at this phase might enhance sympathetic activation which in long run may precipitate cardiovascular diseases. Hence, to explore the autonomic activity to mental stress during this phase of menstrual cycle the study was undertaken. Methods: Thirty apparently healthy young postovulatory female medical students of B. P. Koirala Institute of Health Sciences, Nepal of age 19.93 (± 0.91) years with BMI of 20.70 kg/m2 (± 2.49) kg/m2 were recruited for the present study. Their short term heart rate variability (HRV) of 5 min was recorded during rest at sitting position. Then each subject was given a mental stress (nine questions selected from MENSA workout questionnaire) for 5 min. During the stress, HRV was recorded simultaneously. Data was statistically analyzed using Friedman test followed by multiple comparisons. The p<0.005 was considered statistically significant. Results: Mental stress significantly decreased RMSSD (p= 0.001), NN50 (p= 0.001) and PNN50 (p=0.001) in time domain and HF nu (p=0.012) in frequency domain parameters of HRV. Conclusions: Young healthy post ovulatory females responded to acute mental stress by withdrawing cardiac parasympathetic activity. Keywords: Female; HRV; mental stress